Challenges and practices of academic English communication among Libyan international students in five selected universities in Malaysia - Halali, Ahlam Ali Salim (2022)
Malaysian universities’ use of English in instruction provides Libyan international students, reportedly the seventh largest ethnic group enrolled in Malaysian universities, opportunities to study in various academic fields. However, Libyan students encounter communicative challenges in Malaysian ESL learning environments stemming from insufficient prior EFL learning experience and resultant deficiencies in communicative competence, contributing to communicative language anxiety. Consequently, the students develop mediating learning strategies. Therefore, this study investigated EFL Libyan students’ academic listening and speaking challenges, their mediating learning strategies, and the effects of prior learning experiences and communication language anxiety on their academic communication challenges and strategies. The investigation adopted an explanatory mixed-mode research design with the assistance of Libyan Embassy employing an online questionnaire survey with 223 respondents. Interviews and a focus group discussion were conducted with 20 survey respondents selected through purposive snowball sampling. Field notes and member checks were used for data triangulation and validation. Correlational procedures and structural equation modelling using bootstrapping resampling analyses with SPSS and AMOS were conducted to investigate the cause-and-effect relationships between variables, determine the validity of study models, and test the research hypotheses. NVivo analysis was performed for the interviews and focus group discussion for coding and generating themes from transcript data supported with field notes. The results showed that Libyan students experienced listening comprehension challenges in understanding accents, academic content, and cultural differences. The qualitative results revealed the participants’ listening comprehension in active communication was negatively affected by insufficient prior knowledge of academic terminology and anxiety.The students speaking challenges in academic discourse were due to their inadequate communicative competence and resultant cognitive inhibition. Qualitative analyses revealed students’ reluctance to participate in academic discourse resulted from insufficient academic speaking practice which increased their anxiety, blocking comprehensible input. Thus, the students implemented strategies to improve their academic communication skills. The listening strategies, in ranked order, were metacognitive, cognitive, compensatory, affective, memory-related, and social strategies. The students’ preference for metacognitive and cognitive listening strategies over social strategies was attributed to their negative learning experiences combined with consequential communication anxiety, which discouraged social interaction. Thus, metacognitive and cognitive listening strategies promoted the students’ self-reliance and self-motivation to improve listening comprehension through repetitive listening with reduced anxiety, supporting the storage and retrieval of information between short- and long-term memory. The speaking strategies, in ranked order, were memory-related, metacognitive, affective, compensatory, cognitive, and social strategies. Qualitative results revealed the Libyan students preferred memorisation and self-practice over social strategies. Their reluctance to employ social speaking strategies was because their insufficient prior learning experience resulted in poor communicative competence contributing to communication language anxiety. Memorisation facilitated the students’ mental language modelling, enabling internalisation of their communicative environment. Quantitative analyses revealed the Libyan’s prior learning experiences and communication language anxiety were significantly correlated with their listening and speaking challenges and strategies. It was further found that prior learning experiences and communication language anxiety had mediating effects on the listening and speaking challenges and strategies. Therefore, stakeholders should consider Libyan academic communication challenges resulting from inadequate prior English learning experience affecting their learning success in international higher education through developing and improving English language practice through educational materials and resources that improve English learners’ academic success. Additionally, pre-sessional English programs at Malaysian universities should be aligned with students’ fields of study, emphasising academic terminology enhancing their communicative academic discourse. As the main theoretical components addressed in this research are Piaget’s (1936) cognitive theory, and Krashen’s (1982) affective filter Hypothesis. Therefore, additionally, emphasising the importance of communication theories towards understanding internationals academic communication skills from EFL context by investigating the psychological factors influencing learners’ engagement and cognitive communicative competence enabling internationals to communicate and critically participate and corresponding progression in their learning.